DIFFERENT BITE CLASSES AND THEIR INFLUENCE ON BODY POSTURE: A REVIEW - Cristina Albert; Clara Haddad; Ionut Iulian Lungu; Elena Costescu; Aurel Apintiliesei; Delia Cristina Bahrim; Cătălina Smarandita Morarasu; Alina Stefanache (Romanian Journal of Oral Rehabilitation)
This review explores the relationship between dental occlusion, particularly malocclusion, and its impact on body posture, emphasizing the musculoskeletal effects of different occlusal bite classifications. Class I, II, and III malocclusions affect head, neck, and spine alignment, which can lead to musculoskeletal disorders, chronic pain, and postural imbalances. Class II (overbite) results in anterior head posture, increasing strain on the cervical spine, while Class III (underbite) causes posterior head posture, leading to compensatory stress in the spine and lower back. Research highlights the biomechanical effects of malocclusion on the temporomandibular joint (TMJ) and spine, contributing to conditions like kyphosis, lordosis, and gait abnormalities. A comprehensive search of relevant literature was conducted using databases such as PubMed and Google Scholar. This review identified a need for interdisciplinary treatment approaches combining dental, orthopedic, and physical therapy interventions to address both dental alignment and musculoskeletal health. Orthodontic treatments, such as braces and jaw surgery, help realign the jaw, reducing postural strain, while physical therapy can alleviate muscle tension and improve overall body alignment. These insights highlight the importance of integrating dental and postural treatment strategies for improved patient outcomes.